1994
DOI: 10.1109/72.265960
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary algorithm that constructs recurrent neural networks

Abstract: Standard methods for inducing both the structure and weight values of recurrent neural networks fit an assumed class of architectures to every task. This simplification is necessary because the interactions between network structure and function are not well understood. Evolutionary computation, which includes genetic algorithms and evolutionary programming, is a population-based search method that has shown promise in such complex tasks. This paper argues that genetic algorithms are inappropriate for network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
405
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 878 publications
(438 citation statements)
references
References 25 publications
2
405
0
3
Order By: Relevance
“…assuming a large network, they prune off the superfluous components. However, Angeline et al (1994) indicates that ''Such structural hill climbing methods are susceptible to becoming trapped at structural local minima''. The reasoning behind this is clarified by Miller, Todd, and Hegde (1989), stating that the architecture space is non-differentiable, complex, deceptive and multi-modal.…”
Section: Evolutionary Annsmentioning
confidence: 99%
See 4 more Smart Citations
“…assuming a large network, they prune off the superfluous components. However, Angeline et al (1994) indicates that ''Such structural hill climbing methods are susceptible to becoming trapped at structural local minima''. The reasoning behind this is clarified by Miller, Todd, and Hegde (1989), stating that the architecture space is non-differentiable, complex, deceptive and multi-modal.…”
Section: Evolutionary Annsmentioning
confidence: 99%
“…When used for training ANNs (with fixed architecture), many researchers (Bartlett & Downs, 1990;Hansen & Meservy, 1996;Miller et al, 1989;Prados, 1992;Porto, Fogel, & Fogel, 1995) reported that GAs can outperform BP in terms of both accuracy and speed, especially for large networks. However, as stated by Angeline et al (1994) and Yao and Liu (1997), GAs do not suit well for evolving networks. For instance, the evolution process by GA suffers from the permutation problem (Belew, McInerney, & Schraudolph, 1991), indicating that two identical ANNs may have different representations.…”
Section: Evolutionary Annsmentioning
confidence: 99%
See 3 more Smart Citations